1997
DOI: 10.1192/bjp.170.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of syndromes in schizophrenia

Abstract: Although not directly supporting the first two hypotheses; the results are, in general, consistent with there being different cortical-subcortical circuits associated with each of psychomotor poverty and disorganisation. Temporal lobe functioning appears to have particular significance for the reality distortion syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 24 publications
2
43
0
5
Order By: Relevance
“…The current efforts to search for core impairments that may help on the development of more effective and efficient combinations of psychosocial and pharmacological interventions need to clarify the links between neurocognitive deficits and symptom clusters. Studies have shown that social cognition [40,61] and executive functioning deficits [23,62] are associated with negative symptoms, while verbal fluency deficits have been linked with disorganised symptoms [62]. The more precise dimensions of impairment in mental functioning provided by neuropsychological assessments are likely to refine our understanding of psychiatric phemonenology and to facilitate clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current efforts to search for core impairments that may help on the development of more effective and efficient combinations of psychosocial and pharmacological interventions need to clarify the links between neurocognitive deficits and symptom clusters. Studies have shown that social cognition [40,61] and executive functioning deficits [23,62] are associated with negative symptoms, while verbal fluency deficits have been linked with disorganised symptoms [62]. The more precise dimensions of impairment in mental functioning provided by neuropsychological assessments are likely to refine our understanding of psychiatric phemonenology and to facilitate clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Formal thought disorders have been linked to performance on the highly specific measure of semantic priming [22]. Negative symptoms have been associated with left hemisphere functions, such as making perseverative errors in the Wisconsin Card Sorting Test (WCST), and verbal fluency deficits [23].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has proved informative in that these symptombased syndromes have been associated with specific neuropsychological deficits (Bilder et al 1985;Pantelis & Brewer, 1995 ;Norman et al 1997;Liddle, 2001). The most consistent finding has been an association between a negative symptom-based syndrome (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…[24][25][26][27][28][29] These psychopathological dimensions appear to have distinct genetic and neurocognitive correlates. 30,31 The extent to which analogous dimensions exist in the symptoms of those at high risk of psychosis is unclear. Hawkins et al 32 recently conducted a factor analytic study to examine the construct validity of the Scale of Prodromal Symptoms (SOPS) in an ARMS sample.…”
Section: Introductionmentioning
confidence: 99%